Biogeografia histórica e conservação das serpentes da floresta pluvial atlântica costeira do Brasil - Barbo, Fausto Erritto [UNESP] (2012)
Biogeography aims mainly to identify patterns of species distribution and to propose hypothesis about the process that have shaped those patterns. The distribution patterns are not random and are a result of historical events. The congruence among those distribution patterns, ie the distribution overlap of two or more endemic taxa, delimits an area of endemism, fundamental for formulation of hypothesis in historical biogeography. Areas of endemism in the Atlantic Forest have already been delimited in previous studies. However, there are no studies on snakes for this purpose. In the present study, 83 endemic snake species were identified in the Atlantic Forest. From Parsimony Analysis of Endemicity (PAE) and Endemism analysis (NDM/VNDM), four areas of endemism were proposed: Alagoas, Sul da Bahia, Serra do Mar, and Araucária. From the distribution overlap of snakes and other endemic taxa, additional four areas of endemism were defined: Ilha dos Alcatrazes, Ilha da Queimada Grande, Ilha de São Sebastião, and Northestern Brejos de Altitude. These eight areas of endemism were analyzed in order to quantify the vegetation remnants and protected areas in conservation units. The species delimiting areas of endemism were evaluated in the threat of extinction, according to the IUCN criteria. Four species were considered as “Critically Endangered”, five were “Endangered”, nine “Vulnerable”, and seven as “Near Threatened”. Those areas of endemism must be considered as priorities for conservation as they correspond to unique evolutionary unities and harbor endemic and threatened taxa